Pengaruh Strategi Pembelajaran Berorientasi Aktivitas Siswa (PBAS) Terhadap Hasil Belajar Matematika - Nurdiat, Lara; Imamuddin, M.; Fitri, Haida; Rahmat, Tasnim (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of Student Activity Oriented Learning (PBAS) strategy on mathematics learning outcomes. This pre-experimental study used a research design. Static Group Analysis using Isolated Randomised Control Group Architecture. The demographics of this study consisted of VIII grade students of SMP N 4 Kinali. The sampling technique used was random sampling. In this research sample, Class VIII.3 represented the experimental group, while Class VIII.1 as the control group. The calculation results show that t_(count) is smaller than ttable. This means that the Ho test decision is rejected with a significance level of α = 0.05. At a significance level of α = 0.05, the P value is determined to be 0.001 through Minitab, indicating that the P value is below α. Ho's agreement was rejected, while H1 was granted. The results showed that the application of Student Activity Oriented Learning (PBAS) strategies significantly improved the academic achievement of students in class VIII of SMP N 4 Kinali in the 2023/2024 school year